2009
DOI: 10.1007/s00586-009-0932-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of angled sagittal MRI and conventional MRI in the diagnosis of herniated disc and stenosis in the cervical foramen

Abstract: The object of this study is to demonstrate that angled sagittal magnetic resonance imaging (MRI) enables the precise diagnosis of herniated disc and stenosis in the cervical foramen, which is not available with conventional MRI. Due to both the anatomic features of the cervical foramen and the limitations of conventional MR techniques, it has been difficult to identify disease in the lateral aspects of the spinal canal and foramen using only conventional MRI. Angled sagittal MRI oriented perpendicular to the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 14 publications
2
32
0
3
Order By: Relevance
“…Oblique sagittal images provide much more information about the foramen than routine sagittal images because oblique images are oriented perpendicular to the course of the cervical neural foramen [5]. Facet overgrowth, herniated lateral discs and uncinate process osteophytes that may induce foraminal stenosis are more easily detectable in the oblique sagittal view [8]. A major disadvantage of the oblique sagittal view is that its use increases examination time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oblique sagittal images provide much more information about the foramen than routine sagittal images because oblique images are oriented perpendicular to the course of the cervical neural foramen [5]. Facet overgrowth, herniated lateral discs and uncinate process osteophytes that may induce foraminal stenosis are more easily detectable in the oblique sagittal view [8]. A major disadvantage of the oblique sagittal view is that its use increases examination time.…”
Section: Discussionmentioning
confidence: 99%
“…A major disadvantage of the oblique sagittal view is that its use increases examination time. Shim et al [8] reported that the total scan time on the oblique sagittal view was 5 min. In the present study, we required 3.25 min for the acquisition of both oblique sagittal views, whereas the acquisition time for the routine T 2 weighted sagittal view alone was 2.5 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the intervertebral foramen is located anteriorly to the vertebral canal at an angle of 45 o relative to the coronal plane [19]. Therefore, the oblique or axial views have greater confidence rates than the sagittal views, in order to evaluate the presence of foraminal stenosis or of a disc herniation [17,25,36,37,44]. CT -computed tomography; MRI -magnetic resonance imaging…”
Section: The Bony Borders Of the Intervertebral Foramenmentioning
confidence: 99%
“…Natural aging process outcrops imminent degenerative changes in the cervical spine (CS) consisting instability, disc herniation, and spinal stenosis [1]. The neural foramen of the CS has an almost elliptical shape and is oriented in an oblique position [2,3]. Conventional plain radiographs at an oblique view show the neural foramen of the CS, however they are of limited value in evaluating neural foraminal pathology.…”
Section: Introductionmentioning
confidence: 99%